Treatment of suprasellar arachnoid cyst at children - Orlov, Yu. A.; Shaversky, A. V.; Zynkevich, Ya. P.; Plavskiy, P. N. (Ukrainian Neurosurgical Journal, 2005)
The problems of clinical flow features, diagnostics, comparative description of suprasellar arachnoid cysts treatment methods are considered at children. The material is based on the retrospective analysis of case reports of child patients, being on treatment in clinic for the period for 15 years. Discovered characteristics for suprasellar arachnoid cysts symptoms, the necessity of individual choice of surgical treatment methods are indicated.